Glycated Hemoglobin Level and Body Mass Index Correlation with Peripheral Artery Disease in Patients with Type 2 Diabetes Mellitus at Waled Hospital, Cirebon, Indonesia - Auliya, Tania; Amaliyah, Nihayatul; Herdwiyanti, Menik (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2024)
Background: Peripheral Artery Disease (PAD) is a condition that reduces blood flow to the lower extremities and is primarily caused by atherosclerosis. PAD is one of the complications of Diabetes Mellitus (DM). Diabetics have an 11.6 times more likely to develop PAD than those without diabetes. Glycated haemoglobin (HbA1c) levels >7% are at a higher risk of chronic complications. Obesity and overweight also raise the risk of developing PAD disease. However, research on the correlation between Body Mass Index (BMI) and PAD remains unclear and controversial. Aims: To analyze the correlation between HbA1c levels and BMI with the incidence of Peripheral Artery Disease in patients with type 2 Diabetes Mellitus at Waled Hospital. Methods: This is an analytical observational study with a cross-sectional design. Data was collected on patients diagnosed with type 2 Diabetes Mellitus at the Internal Medicine Clinic at Waled Hospital in June - July 2024. A total sample of 77 was obtained using consecutive sampling. The inclusion criteria were type 2 DM, aged 19-60 years, and medical record data equipped with the HbA1c levels for at least the last 3 months prior to data collection. The exclusion criteria were patients with a history of diabetic ulcers, amputation and limb disability, Acute Coronary Syndrome, stroke, kidney failure, recurrent anaemia, and blood transfusions in the last 3 months. Primary data was gathered through an ABI examination, while secondary data was obtained from medical records. The data was analysed using the Spearman correlation test. Results: Patients had poor HbA1c control (51.9%), moderate HbA1c control (29.9%) and good HbA1c control (18.2%), with the majority of patients had normal BMI (39%) followed by obese I (22.1%), overweight and obese II (16.9%). Our study showed that the distribution of PAD levels was severe (0%), moderate (3.9%), mild (44.2%), normal (46.8%), and arteriosclerotic (5.2%). The correlation test showed p-0.789 (p> 0.05) for HbA1c levels with PAD and p- 0.653 (p>0.05) for BMI with PAD. Conclusion: There was no association between glycated hemoglobin or Body Mass Index values and the incidence of PAD in patients with type 2 Diabetes Mellitus at Waled Hospital, Cirebon, Indonesia. Received: 25 September 2024 | Reviewed: 21 October 2024 | Revised: 30 November 2024 | Accepted: 11 December 2024.